Dispensa de licitação por emergência: uma proposta gerencial - Rodrigues, Arquimedes Guedes (2020)
In public administration, hiring is linked to all legislation that makes up Administrative Law. They are fixed by the Annual Budget Law (LOA), and are effectively carried out under public management. The general rule for selection the most advantageous proposals for contracting is bidding. There are, however, some exceptions that are expected to be executed under the rite of the Bidding Exemption, one of which is based on emergency cases, for urgent answer. (Federal Act n. 8.666/93. Art. 24, IV) For such a situation to be well characterized, the demand that indicates the Bidding Exemption must demand prompt attention to the supply of materials or in the provision of services, involve the safety of people or property, public or private, and follow a differentiated formalization that also removes some cautions typical of normal bidding, which aim to guarantee publicity, competitiveness and market access. In some cases, bidding exemptions occur due to fictitious emergency situations, that is, that have come into existence, or have been aggravated, due to the lack of due planning, administrative negligence or, as it is known in the TCU (Federal Audit Court) case law, ‘fabricated emergency’. In this context, the objective of this research is to verify the occurrence of Bidding Exemptions by emergency in the Ministry of Health of the Federal Government in the period from 2015 to 2020. It focuses on the purchase of the ten most exceptional drugs purchased by the aforementioned body due to court orders, associating them to the jurisprudence on the subject at the Federal Audit Court. During the analysis of the results, a set of important elements was identified: the relationship between expenditure planning, its realization through Bidding Exemption, the transparency of these expenses and their implications for the treasury that allowed the development of managerial proposals that promote changes to mitigate costs and risks arising from inadequate management.